Linking seasonal forecasts into risk - view to enhance food security contingency planning - Hansen, James; Tippett M; Bell, M.; Ines, Amor V.M. (International Research Institute for Climate and Society, 2010)
RiskView is a tool developed by the World Food Programme (WFP) to translate weather data (real-time and historical) and other spatial information (e.g., crops, drought risk, population, etc.) into food security needs and response costs. It serves as a swift way of estimating costs in advance of food insecurity outlooks for financial planning, and for facilitating better resource allocations to disasters before on-the-ground needs assessments are produced. One of the cores of RiskView is the calculation of Water Requirement Satisfaction Index (WRSI) to estimate drought risks at the aggregate scale. WRSI is used to determine the risk of a region being food insecure in a coming season. To accomplish this, RiskView applies a forward- looking approach in which observed rainfall from the current season is used to calculate WRSI up to the current date, then samples rainfall from historical years to calculate WRSI for the remaining part of the cropping season. This forward-looking approach allows RiskView to include estimates of uncertainty in the calculations of WRSI from historical information. However, this capability could potentially be enhanced by using seasonal climate forecasts to weight historical years instead of assigning them equal weights. For this reason, WFP partnered with IRI to develop weights to be applied to WRSI values calculated for administrative regions in Africa. These would weight projections of end-of-season WRSI values based on the IRI Net Assessment seasonal precipitation forecasts. In RiskView, for a particular agricultural or pastoral season and administrative region, WFP calculates projected end-of-season WRSI values based upon historical RFE precipitation estimates from previous seasons (beginning with 1996) to reflect potential uncertainty in the projected WRSI estimate. The IRI weights based upon the latest IRI Net Assessment seasonal precipitation forecast would be applied to the historical end-of-season WRSI values from previous seasons to provide a forecast-based shift in the PDF to adjust the projected end-of-season WRSI values for the current agricultural or pastoral season of interest. This report outlines the procedure used to develop these weights and how it can be incorporated within Africa RiskView and its outputs.